An Increased Aspartate to Alanine Aminotransferase Ratio Is Associated With a Higher Risk of Cognitive Impairment - Li, Wei; Yue, Ling; Sun, Lin; Xiao, Shifu (Frontiers in Medicine, 2022)
Abstract Background:Recent Alzheimer's disease (AD) hypotheses implicate that hepatic metabolic disorder might contribution to the disease pathogenesis of AD, but the mechanism remains unclear. Aims: To investigate whether the elevated aspartate aminotransferase (AST) and Alanine aminotransferase (ALT) ratio is associated with future cognitive decline, and to explore the possible mechanisms of liver enzymes affecting cognitive function. Methods: Three different clinical cohorts were included in the current study, including one cross-sectional study(Cohort 1) and two longitudinal follow-up studies(Cohort 2 and 3). All participants completed a detailed clinical evaluation, neuropsychological tests, and liver enzyme tests. In addition, some of them also underwent structural magnetic resonance imaging (MRI) scans. Results: Cohort 1 was derived from the CRC2017ZD02 program, including 135 amnestic mild cognitive impairment (aMCI) patients, 22 AD patients, and 319 normal controls. In this cross-sectional study, we found that the AST/ALT ratio was associated with AD (p=0.014, OR=1.848, 95%CI: 1.133~3.012), but not aMCI; Cohort 2 was derived from the Shanghai Brain Health Program. A total of 260 community elderly people with normal cognitive function were included in the study and followed up for two years. In this two-year longitudinal follow-up study, we found that higher AST/ALT ratio was a risk factor for future development of MCI(p=0.014, HR=1.848, 95%CI: 1.133~3.021); Cohort 3 was derived from the China longitudinal aging study(CLAS) Program. A total of 97 community elderly people with normal cognitive function were followed up for seven years, and all of them completed MRI scans. In this seven-year longitudinal follow-up study, we found that higher AST/ALT ratio was a risk factor for future development of MCI (p=0.007, HR=2.245, 95%CI: 1.245~4.046), and the AST/ALT ratio was negatively correlated with right hippocampal volume(r=-0.148, p=0.043). Conclusions: An increased ratio of AST to ALT is associated with a higher risk of cognitive impairment and may impair cognitive function by affecting hippocampal volume Keywords: AST, ALT, hippocampal, cogntive function, eldely